PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PEREDARAN JAJANAN ANAK SEKOLAH BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 dan UNDANG-UNDANG NOMOR 18 TAHUN 2012 (STUDI TERHADAP PERMEN JELI STIK TAHUN 2018 DI KENDAL) - A.M Tri Anggraini; Marcella Wanda Raditya (Faculty of Law - Tarumanagara University, 2019)
Technological advances have brought rapid and significant changes to the food industry. By using modern technology, the food industry is now able to produce on a very large scale including a variety of products with a very wide